Effects of a multimodal exercise program on the functional capacity of Parkinson's disease patients considering disease severity and gender - Orcioli-Silva, Diego [UNESP]; Barbieri, Fabio Augusto [UNESP]; Simieli, Lucas [UNESP]; Rinaldi, Natália Madalena; Vitório, Rodrigo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (FapUNIFESP (SciELO), 2014)
The purpose of this study was to investigate the effects of a multimodal exercise program (MEP) on the functional capacity of patients with Parkinson’s disease (PD) according to disease severity and gender. Fourteen patients with PD participated in the study and were distributed into groups according to 1) stage of disease and 2) gender. Functional capacity was evaluated before and after 6 months of intervention. The overall PD patient group improved their coordination and strength. Men and women improved in strength performance after exercise. Men also improved on coordination. For severity of disease, the unilateral group improved in strength, while the bilateral group improved in strength, balance, coordination and the UPDRS-functional score. In conclusion, a MEP is efficient in improving components of functional capacity in patients with PD, especially in strength. Gender may be considered in the exercise program. Individuals in the bilateral disease group appeared to benefit more from exercise.

Efectos de un programa de ejercicio multimodal en la capacidad funcional de los pacientes con enfermedad de Parkinson teniendo en cuenta la gravedad de la enfermedad y el sexo”. Esto estudio investigó el efecto de un programa de ejercicio multimodal (PEM) en la capacidad funcional de pacientes con enfermedad de Parkinson (EP), considerando la severidad de la enfermedad y el género. Catorce pacientes con EP participaron del estudio, distribuidos en grupos: 1) severidad de la enfermedad, 2) género. La capacidad funcional fue avaluada antes y después de 6-meses de intervención. En general, los pacientes mejoraron coordinación y fuerza. Hombres y mujeres mejoraron el desempeño de la fuerza después del ejercicio. Todavía, los hombres también mejoraron coordinación. Considerando la gravedad de la enfermedad, el grupo unilateral mejoró fuerza y el grupo bilateral mejoró fuerza, equilibrio, coordinación y la UPDRS-funcional. Así, el PEM fue eficaz en mejorar los componentes de la capacidad funcional de pacientes con EP, especialmente la fuerza. El género debe ser considerado en el programa de ejercicios. Individuos con enfermedad bilateral parecen beneficiarse más de los ejercicios.

Efeitos de um programa de exercícios multimodal na capacidade funcional de pacientes com doença de Parkinson considerando a gravidade da doença e sexo”. O objetivo deste estudo foi investigar o efeito de um programa de exercício multimodal (PEM) na capacidade funcional de pacientes com doença de Parkinson (DP), de acordo com a severidade da doença e gênero. Catorze pacientes com DP participaram do estudo, distribuídos em dois grupos: 1) severidade da doença, 2) gênero. A capacidade funcional foi avaliada antes e após 6 meses de intervenção. Em geral, os pacientes melhoraram a coordenação e força. Homens e mulheres melhoraram o desempenho da força após o exercício. Os homens também melhoraram a coordenação. Para a severidade da doença, o grupo unilateral melhorou a força, enquanto o grupo bilateral melhorou força, equilíbrio, coordenação e UPDRS funcional. Portanto, o PEM é eficiente na melhoria dos componentes da capacidade funcional de pacientes com DP, especialmente a força. O gênero deve ser considerado no programa de exercício. Pacientes no estágio bilateral parecem ter mais benefícios do exercício.
Keywords: Multimodal exercise program; Functional capacity; Parkinson’s disease; Programa de ejercicio multimodal; Capacidad funcional; Enfermedad de Parkinson; Programa de exercício multimodal; Capacidade funcional; Doença de Parkinson